Model Manajemen Pembelajaran Online Pada Pendidikan dan Pelatihan Guru Pendamping Muda PAUD - Natalia Dewi Mumpuni; Bambang Ismanto (Universitas Kristen Satya Wacana, 2019)
The purpose of this study is to (1) Explain the Implementation of Education and Training of young assistant teachers in Central Java; (2) Explain the weaknesses of the education and training of young assistant teachers in Central Java; (3) Describe the Educational Management Model and training of PAUD young assistant teachers through online media. Early Childhood Teacher Education and Training is a series of tiered PAUD teacher education and training owned by the Ministry of Education and Culture that can be organized by institutions that meet the requirements or have been designated as training providers. Online media used in this research are Information Systems and Video Conference Webex cisco meetings. The final product of this research is a model and supporting material in the form of a guide, which consists of a guide for participants, a guide for field officers and a guide for facilitators. This research and development uses a mixed method, using the seven steps of development from Borg and Gall, which is integrated with the ADDIE model. Data collection methods use instruments in the form of questionnaires, interview guidelines, and tests. The research subjects were organizers, field officers, facilitators, and training participants. Data analysis techniques using quantitative and qualitative descriptive. The results of the main trial phase showed that the education and training of PAUD young teacher assistants through online media was effective in increasing competency, this was seen from the increase in pre-test to post-test average points which rose 32 points and the graduation rate of participants was 98.2%.